Intelligent day-ahead optimization scheduling for multi-energy systems - Yufeng, Yang; Zhicheng, Zhou; Xubing, Xiao; Yaxin, Pang; Linjun, Shi (Frontiers in Energy Research, 2024)
Concerning energy waste and rational utilization, this paper studies the optimal scheduling of dayahead energy supply and the community's demand with a combined cooling, heating, and power (CCHP) system in summer. From the perspective of bilateral costs and renewable energy use, this paper examines the impact of energy storage systems integrated into cogeneration systems. The Gurobi solver is utilized to optimize the residential community's supply and demand sides of the traditional CCHP system (T-CCHP) and the CCHP system with energy storage (CCHP-ESS) under insufficient solar power. Subsequently, two optimal arrangements for energy consumption on the user side under these systems are suggested. In the optimization model, energy storage is added to the traditional CCHP system on the energy supply side. On the user side, the energy use scheme is optimized considering the user's comfort. The innovation point of this study is that the optimization of comprehensive energy in the park involves both supply and demand. The impact of increasing energy storage is discussed on the energy supply side, and the impact of optimization of the energy use plan on cost is discussed on the user side.